Hematopoietic stem cell transplantation for thalassemia. (September 2012) - Elborai, Yasser; Uwumugambi, Alain; Lehmann, Leslie
Thalassemia is an autosomal recessive disorder associated with defective synthesis of the α- or β-chain of hemoglobin. For β-thalassemia major patients, therapeutic options are either monthly red cell transfusions and chelation therapy or allogeneic stem cell transplant. Patients undergoing transfusion therapy remain at risk for transmitted infections and iron overload with associated tissue damage. Stem cell transplant is the only curative approach and success is inversely correlated with the degree of iron overload and hepatic damage. Overall outcomes following stem cell transplant with a matched sibling donor are excellent with over 90% of low-risk children becoming transfusion free. Hypertransfusion therapy and aggressive chelation in addition to hydroxyurea, azathioprine and fludarabine is a new approach for high-risk patients to decrease graft rejection by suppressing endogenous erythropoiesis pretransplant. The use of unrelated donors and novel approaches such as gene therapy are under current investigation.